Diversity of faunal communities in the Biodiversity Park of Ciherang, Bogor, West Java, Indonesia - HENDRA GUNAWAN; SUGIARTI SUGIARTI; ANITA RIANTI; VIVIN SILVALIANDRA SIHOMBING (Biodiversitas Journal of Biological Diversity, 2016)
Gunawan H, Sugiarti, Rianti A, Sihombing VS. 2016. Diversity of faunal communities in the Biodiversity Park of Ciherang, Bogor, West Java, Indonesia. Biodiversitas 17: 479-486. A Biodiversity Park is a new concept for ex situ conservation in Indonesia which was first launched in 2012. The purposes of a Biodiversity Park are to conserve indigenous and threatened species of flora, provide habitat for a diversity of animals, and to provide opportunities for economic benefit, recreation, education and research. The main goal of Biodiversity Park is to increase flora and fauna diversity in the midst of human settlement and industrial precincts. This research was directed at studying the diversity of faunal communities in the Biodiversity Park of Aqua Danone Ciherang, Bogor, West Java, Indonesia. Line transects, walk transects, terrestrial transects and point count methods were combined to census the mammals, reptiles, amphibians and birds in the Biodiversity Park. Twenty five families of fauna were identified, consisting of 28 genera and 32 species. The Shannon diversity index for the total faunal community was 2.82. Composition of the faunal community consisted of birds (66%), reptiles (16%), mammals (12%) and amphibians (6%). This finding supports the goal that Biodiversity Park can increase flora and fauna diversity. The diversity index of 2.37 for the bird community indicates a beneficial contribution to habitat quality within an urban environment.